2020
DOI: 10.1186/s12916-020-01835-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of HIV self-testing to standard HIV testing for key populations: a systematic review and meta-analysis

Abstract: Background We update a previous systematic review to inform new World Health Organization HIV self-testing (HIVST) recommendations. We compared the effects of HIVST to standard HIV testing services to understand which service delivery models are effective for key populations. Methods We did a systematic review of randomised controlled trials (RCTs) which compared HIVST to standard HIV testing in key populations, published from 1 January 2006 to 4 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 43 publications
6
141
2
Order By: Relevance
“…Previous studies have investigated the experiences of trans people with HIVST in other (non-European) settings; this work adds weight to the conclusion that HIVST is highly acceptable to this group in a range of settings [18,20,32]. We also demonstrate significant unmet testing need; 31% of trans men and women had not previously tested for HIV, this is more than double the 15% of MSM (cis and trans combined) from the wider trial who had not previously tested [33].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previous studies have investigated the experiences of trans people with HIVST in other (non-European) settings; this work adds weight to the conclusion that HIVST is highly acceptable to this group in a range of settings [18,20,32]. We also demonstrate significant unmet testing need; 31% of trans men and women had not previously tested for HIV, this is more than double the 15% of MSM (cis and trans combined) from the wider trial who had not previously tested [33].…”
Section: Discussionsupporting
confidence: 52%
“…Analysis combined framework and thematic approaches [26,27]. Our framework drew from emerging themes identified during data generation, the wider literature around trans peoples' experiences of HIVST / sexual health services, theorised key components of intervention acceptability from formative and RCT acceptability work and systematic reviews [18,23,[28][29][30]. The analysis framework can be found in additional file 3.…”
Section: Interviews and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…HIVST may be especially well-suited for key populations, including men who have sex with men (MSM) and female sex workers (FSWs), by addressing additional barriers these populations face to facility-based testing (e.g., stigma, discrimination, and inconvenient clinic hours). In this study, Dr. Witzel and colleagues conducted a systematic review and meta-analysis to understand the effect of HIVST versus standard facility-based HIV testing for key populations [4]. Overall, the authors found that HIVST increased testing uptake, frequency, and yield of positive results for cisgender MSM and transgender persons but not for FSWs.…”
mentioning
confidence: 99%
“…We also compare their positions to those expressed by MSM who are one of the most relevant groups of PUs. HIV self-testing has proven to be a reliable testing option [17] and has shown its capacity to increase testing uptake under experimental conditions [18]. According to the European Centre for Disease Prevention and Control (ECDC), it needs to be made available to MSM in order to increase testing uptake and frequency of testing [19].…”
Section: Discussionmentioning
confidence: 99%